Reviews of new publications - Holmes, Derek A (KUKILA, 1997)
Jepson, P. & R. Ounsted (eds.). Birding Indonesia: a Bird-watchers Guide to the Worlds Largest Archipelago. Periplus Action Guides. Periplus Editions (HK) Ltd. Whitten, T., Roehayat Emon Soeriaatmadja & Suraya A. Afiff. The Ecology of Java and Bali. The Ecology of Indonesia Series MacKinnon, K., Gusti Hatta, Hakimah Halim & A. Mangalik. The Ecology of Kalimantan. The Ecology of Indonesia Series Holmes, D. & K. Phillipps. 1996. The birds of Sulawesi. Oxford University Press: Kuala Lumpur